ANALYSIS OF ZHONGDANG PAN AND GERALD M KOSICKI’S FRAMING ON NEWS REJECTION OF ROHINGNYA REFUGEES IN ACEH BESAR (STUDY ON ANTARANEWS.COM AND DETIK.COM) - Pertiwi, Cholidah Astri; Pitoyo, Pitoyo; Ramadhani, Rizky Wulan; Utami, Sabrina Rahma (Universitas Gunadarma, 2024)
This research aims to analyze the framing techniques of Antaranews.com and Detik.com media in reporting on Rohingya refugees on December 11 2023. This is interesting because the two media come from different ownership; Antaranews.com is managed by the Antara National News Agency (LKBN Antara), which is a State-Owned Enterprise (BUMN) in the news agency sector, while Detik.com is under the private company PT Trans Digital Media. The author uses the framing analysis model of Zhong Dang Pan and Gerald M. Kosicki to divide this news frame into 4 structural dimensions, namely syntax, script, thematic and rhetorical. The results of the research show that the framing of news about the rejection of Rohingya refugees in Aceh on December 11 2023 written by Antaranews.com was more balanced than Detik.com in presenting the news. The selection of quotes and photos included makes the reporting construction carried out by Antaranews.com try to direct public opinion to see from both sides, the Rohingya refugees and the residents of Ladong Aceh Besar. Meanwhile, Detik.com has not fulfilled the 5W+1H principle and does not write news from both sides of the point of view.